Validation of the International Tumor Budding Consensus Conference (2016) recommendations in oral tongue squamous cell carcinoma. (15th April 2019) - Xie, Nan; Yu, Pei; Liu, Haichao; Liu, Xiqiang; Hou, Jinsong; Chen, Xiaohua; Huang, Hongzhang; Wang, Cheng
Abstract: Background: Tumor budding is a valuable prognostic marker in oral tongue squamous cell carcinoma (OTSCC) but lacks a standardized scoring system. The aim of this study was to evaluate the prognostic value of tumor budding for OTSCC patients based on the scoring system recommended by the International Tumor Budding Consensus Conference (ITBCC) 2016. Methods: Tumor budding was scored as ITBCC recommended in 255 patients with OTSCC. Then, associations between tumor budding and clinicopathologic parameters were examined. Among them, 136 patients with follow‐up data available were used to evaluate overall survival (OS) by the Kaplan‐Meier method. Prognostic value of tumor budding was assessed by Cox regression analysis. The inter‐observer and intra‐observer agreement was calculated by the kappa statistic. Results: Tumor budding score was associated with lymph node metastasis, differentiation, invasive pattern, lymphoid infiltrate, tumor relapse, invasive depth, and reduced OS in OTSCC patients. The Cox analysis showed high budding score was an independent prognostic factor in patients with all clinical stage and patients with clinical early‐stage OTSCC. The high kappa values were achieved in intra‐observer and inter‐observer. Conclusions: International Tumor Budding Consensus Conference scoring system is a simple, reliable, and reproducible method to measure tumor budding in OTSCC, which should be included in the routine pathological report.